1999
DOI: 10.1557/proc-565-247
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Polysilsesquioxanes - Polysilsesquioxanes as a Candidate to a Low Dielectrics for Electronic Devices -

Abstract: Polysilsesquioxanes PSSQ as a candidate of coatings for interlayer low dielectric films were synthesized by acid and base catalyzed hydrolytic polycondensation of RSi(OMe)3 (R=methyl, vinyl, 3-methacryloxypropyl). Dip and spin coating of PSSQ on organic and inorganic substrates followed by curing at 100 °C, 400 °C, and 450 °C provided transparent and tough coating films of thickness 2000–9000 A. Polysilsesquioxanes adhered strongly to the substrates to form coating films of which the adhesion strength and hard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…This vitrification or cross-linking step is a typical network-forming meth-odology in systems involving OSG precursors as the matrix material. [16][17][18][19] The mechanical properties of many of these systems have been investigated. 4,[20][21][22][23] Most researchers have concluded that silicon bound to nonbridging structures results in a lowering of the hardness and modulus values.…”
mentioning
confidence: 99%
“…This vitrification or cross-linking step is a typical network-forming meth-odology in systems involving OSG precursors as the matrix material. [16][17][18][19] The mechanical properties of many of these systems have been investigated. 4,[20][21][22][23] Most researchers have concluded that silicon bound to nonbridging structures results in a lowering of the hardness and modulus values.…”
mentioning
confidence: 99%